2020
DOI: 10.1039/c9fd00099b
|View full text |Cite
|
Sign up to set email alerts
|

Critical assessment of wet-chemical oxidation synthesis of silicon quantum dots

Abstract: The wet-chemical Si QD synthesis by oxidation of magnesium silicide (Mg2Si) with bromine (Br2) was revisited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 118 publications
(122 reference statements)
1
10
0
Order By: Relevance
“… 7 , 19 22 Such SiNPs are typically synthesized by wet-chemical methods that involve higher temperatures in the presence of carbon sources during the synthesis process that has been recently reported to lead to the cosynthesis of various carbon-related fluorescent material, such as carbon dots 23 25 along with the SiNPs in the sample. Recent critical reports have also shown that even without Si precursors, the product still has optical properties similar to those reported for SiNPs, 26 28 which strengthens the argument of contamination by brightly fluorescent carbon species causing the reported bright PL, instead of silicon.…”
Section: Introductionsupporting
confidence: 71%
“… 7 , 19 22 Such SiNPs are typically synthesized by wet-chemical methods that involve higher temperatures in the presence of carbon sources during the synthesis process that has been recently reported to lead to the cosynthesis of various carbon-related fluorescent material, such as carbon dots 23 25 along with the SiNPs in the sample. Recent critical reports have also shown that even without Si precursors, the product still has optical properties similar to those reported for SiNPs, 26 28 which strengthens the argument of contamination by brightly fluorescent carbon species causing the reported bright PL, instead of silicon.…”
Section: Introductionsupporting
confidence: 71%
“…as precursors is another solution-based method. 67,68 For instance, Fe-doped Si NPs were constructed by the reaction of Na 4 Si 4 with x% Fe (x = 1, 5, 10) and NH 4 Br. 57 The reduction of silicon alkoxide [such as triethoxysilane and (3-aminopropyl) triethoxysilane] is a simple and moderate strategy for watersoluble Si QDs that has been widely reported in recent years.…”
Section: ■ Synthesis Of Si Qdsmentioning
confidence: 99%
“…[44] Wet chemical techniques or chemical oxidation usually used semiconductor as a doping, such as Si/Ge QD. [45] , or H 2 SO 4 or mixed oxidative with HNO 3 can also be used. This technique was used to produce various ROS or oxygen atoms in the form of ÀCOOH and ÀOH.…”
Section: Synthesized Cdsmentioning
confidence: 99%